Unexpected Elevation of Infection Parameters in a Heart Transplanted Patient with Chronic Kidney Disease: A Case Report - JT, Kurzhagen; SS, Roeder; J, Müller-Deile (Archives of Clinical and Medical Case Reports, 2022)
Patients with end-stage kidney disease are under an increased risk for morbidity and mortality due to cardiovascular reasons. Yet, patients might show only atypical symptoms during cardiac events and routinely performed pre-transplant diagnostic measures are discussed controversially. A heart transplanted 50-year-old male with end-stage kidney disease was assessed for kidney transplantation. Myocardial scintigraphy, chest x-ray, pulmonary function test, urological and gastrointestinal assessment showed normal results. A routinely performed blood test revealed elevated procalcitonin, C-reactive protein and leucocytes. Measured vital parameters and physical examination revealed no pathologies. Coughing, shortness of breath or chest pain were denied. CT-scan showed no signs of infection but lack of contrast media enhancement in the heart. Myocardial infarction was confirmed in electrocardiogram and transthoracic echocardiogram demonstrated an impaired ejection fraction of 20%. Treatment with anti-platelet medication and anticoagulation was followed by invasive heart catheterization, which revealed no acute stenosis but a dissolved in-stent thrombosis. Since kidney failure was progressing the patient required dialysis treatment. Microbiological analyses of blood and urine samples stayed negative. Chronic kidney disease patients are at increased cardiovascular risk. However, invasiveness of cardiac diagnostics for potential kidney transplant is debated controversially. KDIGO guideline 2020 advises non-invasive screening for coronary artery disease for asymptomatic patients at high risk. However, there is no specific guideline for previously heart transplanted candidates for kidney transplant and patients with high pretest probability benefit from invasive diagnostics. A risk stratification for cardiac complications and pre-kidney transplant evaluation should be executed in clinical practice.